The Beginnings of Polish Musicology - Sieradz, Małgorzata (Eastern European Studies in Musicology, 2020)
The book presents the history of the only strictly scientific Polish musicological periodical Kwartalnik Muzyczny. It shows how the editorial board of the periodi-cal met with true approval and harsh criticism. The subject allows the author to present the beginnings of Polish musicology and its evolution through three epochs: the late partitioning period, the interwar period of Poland's independ-ence, and the early years after the Second World War